Serum fibrinogen levels and lung fibrosis in COVID-19 patients - Marhana, Isnin A; Anggoro, Adhitri; Semedi, Bambang P; Maimunah, Ummi; Lefi, Achmad; Wiratama, Priangga A; Kusumastuti, Etty H; Rinjani, Lalu GP; Rosyid, Alfian N; Indrawanto, Dwi W (The Journal of Infection in Developing Countries, 2026)
Introduction: Coronavirus disease-2019 (COVID-19) has been declared a global pandemic. Along with multi-organ failure, increased fibrinogen occurs in severe disease and is converted to fibrin, which can trigger pulmonary fibrosis. This study aimed to analyse the correlation between serum fibrinogen levels and the occurrence of lung fibrosis in COVID-19 patients using the core biopsy technique. Methodology: This was a prospective observational study in patients who died during severe COVID-19 treatment in the intensive care unit of a tertiary hospital. Serum fibrinogen levels were measured using a Sysmex Coagulometer based on the Clauss method, which is an automated coagulometric technique. The core biopsy procedure was performed in fibrotic areas identified by radiological imaging. The degree of lung fibrosis according to the Ashcroft scale. Results of fibrinogen levels, fibrosis incidence, and the degree of fibrosis were compared. Results: There was an increase in fibrinogen with a mean level of 616.14 mg/dL, and 35 of 37 samples were positive for fibrosis. The Ashcroft scale score of 5 was the most common fibrosis degree (37.8%). Fibrosis was found among COVID-19 lung biopsies, and fibrinogen also tends to increase in lung fibrosis based on the Ashcroft score, despite no significant correlation between the serum fibrinogen levels and lung fibrosis degree (p = 0.716). Conclusions: Pulmonary fibrosis was frequently observed in lung biopsy specimens from patients with fatal COVID-19. Serum fibrinogen levels tended to be higher in patients with fibrosis, they were not significantly associated with fibrosis severity as assessed by the Ashcroft scale.